Durham Miners Association statement on Strikes, 1943 (pg. 1) (Durham, 1943)
1943 1939-1945 "Durham Miners Association statement on Strikes, 1943 (pg. 1)" [HFR0073a], 1943 This statement from the Durham Miners' Association accepts the restrictions of the Essential Works Order, condemns unofficial strikes as sabotaging the war effort and helping the enemy, and calls for loyalty and discipline.